(untitled) (Educational Dimension, 2021)
The paper analyzes the results of the introduction of the distance learning form (DLF) using electronic educational resources (EER) and the teacher’s virtual classroom in primary school. The experiment took place within the framework of the “Smart Kids” All-Ukrainian project during the long quarantine caused by the COVID-19 pandemic. The educational process took place both synchronously and asynchronously. The present paper substantiates the model of organization of distance learning of primary school students using EER and outlines its three main components: the organization of learning; conducting online classes (explaining new material or practicing skills by students) and monitoring the quality of students’ independent performance of tasks. The results of the experiment prove that it is necessary to provide teachers and students with computer equipment, Internet access, digital resources for teaching and assessment to implement DLF. It has been established that EER in distance learning can be used both on a regular basis – in each class, and periodically – to explain new material or train skills; the quality of tasks performed by students can be monitored in the virtual office of the teacher and shape an individual trajectory of students’ development. The teachers identified the following main problems of DLF implementation: internet interruptions; problems with providing new computer equipment to students and some teachers; lack of state aid in providing EER to all participants in the educational process; limited access to students’ computers during complete isolation due to online work of parents. Despite the outlined problems, the quality of distance learning of primary school students during the pandemic using EER was positively and highly assessed by teachers.